2010
DOI: 10.1353/csd.2010.0023
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Model Minority Myth: Experiences of Filipino American Graduate Students

Abstract: Filipino Americans are one of the largest immigrant groups in the United States and the second largest Asian American/Pacific Islander ethnic group. However, there is little research focusing on the unique experiences of this group, particularly in higher education. This paper presents a qualitative exploration of the experiences of Filipino American graduate students utilizing consensual qualitative research methodology. Results were categorized into domains and themes, with an example of a domain being "defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Our findings also confirmed previous research on the experiences of URM students (Clark et al, 2012;Gomez et al, 2011;Maton et al, 2011;Nadal et al, 2010;Solorzano et al, 2000) in that URM students were more likely than non-URM students to experience micro-aggressions. Our SEM analysis showed that URM students and non-URM students did not differ in how academic environments (i.e., professional relationships, microaggressions and microaffirmations) affected their sense of belonging.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings also confirmed previous research on the experiences of URM students (Clark et al, 2012;Gomez et al, 2011;Maton et al, 2011;Nadal et al, 2010;Solorzano et al, 2000) in that URM students were more likely than non-URM students to experience micro-aggressions. Our SEM analysis showed that URM students and non-URM students did not differ in how academic environments (i.e., professional relationships, microaggressions and microaffirmations) affected their sense of belonging.…”
Section: Discussionsupporting
confidence: 91%
“…Microaggressions may be unconsciously delivered and often take the form of subtle slights, snubs, and questions about one's ability and belonging (Solorzano, Allen, & Carroll, 2002;Solorzano, Ceja, & Yosso, 2000;Sue et al, 2007). Research found that the experience of microaggressions in academic and social spaces on campus negatively influences retention, perception of the campus climate, and academic success (Clark, Mercer, Zeigler-Hill, & Dufrene, 2012;Gomez, Khurshid, Freitag, & Lachuk, 2011;Maton et al, 2011;Nadal, Pituc, Johnston, & Esparrago, 2010;Solorzano et al, 2000;Van Ryzin, Gravely, & Roseth, 2009;Walton & Cohen, 2007;Yosso, Smith, Ceja, & Solorzano, 2009). Although microaggressions have not been studied specifically as they relate to graduate student sense of belonging, previous research suggests to us that they could negatively impact graduate student sense of belonging.…”
Section: Microaffirmations and Microaggressionsmentioning
confidence: 99%
“…For instance, Latina/o and African American students reported feelings of self-doubt when faced with microaggressions in their academic environment (Solórzano et al, 2000;Yosso et al, 2009), while Black men and Latina women reported a sense of not belonging after being targeted by exclusionary microaggressions (McCabe, 2009). A study with Filipino American graduate students found that experiences with racial microaggressions, overt racism, and systemic racism often led to feelings of marginalization and disconnect from their institutions; furthermore, students reported feeling isolated and misunderstood because of their ethnicity (Nadal, Pituc, Johnston, & Esparrago, 2010). Given all of these, it clear that students of color encounter discrimination, alienation, invisibility, and invalidation and that the cumulative nature of these experiences may all be harmful to their development and self-concept.…”
Section: Self-esteem People Of Color and College Studentsmentioning
confidence: 99%
“…Graduate students of color experience microaggressions perpetuated by peers and faculty at individual, institutional, and structural levels (Gildersleeve, Croom, & Vasquez, 2011;Nadal, Pituc, Johnston, & Esparrago, 2010). Racial microaggressions directed toward graduate students include assumptions of criminality; ascriptions of intelligence (Sue, Lin, Torino, Capodilupo, & Rivera, 2009;Torres, Driscoll, & Burrow, 2010); allegations of oversensitivity and white student denial of racism (Clark, Spanierman, Reed, Soble, & Cabana, 2011); isolation, marginalization, and tokenization (Gildersleeve, Croom, & Vasquez, 2011;Torres, Driscoll, & Burrow, 2010); questioning of credibility (Gomez, Khurshid, Freitag, & Lachuk, 2011); white faculty's fear of providing challenging feedback (Constantine & Sue, 2007); and expressions of paternalistic adoration (Clark, Spanierman, Reed, Soble, & Cabana, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%